EVALUASI PROGRAM DESA MANDIRI INFORMASI BERBASIS APLIKASI ANDROID SISTEM INFORMASI DESA (SIFORDES) - Suranto Aw (Universitas Negeri Yogyakarta, 2018)
This study aims at investigating the effectiveness of using android application-based village Information System (abbreviated as